Effect of Special physical exercises on developing power define by speed and agility for football assistant referees - abass, karrar; Abd Alsatar, Muhanad (Journal of Physical Education, 2023)
The study aimed to prepare physical exercises on developing power defined by speed and agility for first-degree football assistant referees and to identify the effect of physical exercises on developing power defined by speed and agility for first-degree football assistant referees. The researchers used the experimental method, on (10) assistant referee in each experimental and control group. The researcher applied the experiment using training tools and (4) training sessions for eight weeks. The results showed significant effect on power define by speed and agility test in both groups in favor of experimental group.